Philippine indigenous dairy products improved with probiotic bacteria - Kisworo, Djoko; Elegado, Francisco B.; Barraquio, Virginia L. (2008)
The study determined some probiotic properties of locally isolated lactobacilli strains in order to select a good probiotic inoculum for indigenous dairy products. Six selected isolates from two commercial probiotic dairy products - Lactobacillus paracasei subsp. paracasei 1C10, 2C10, 3C10, 2Y9, 3Y9 and Enterococcus faecalis 1Y9 - were subjected to antimicrobial/bacteriocin activity assay against selected indicator strains and resistance to gastro-intestinal tract (GIT) conditions such as tolerance to artificial gastric juice and simulated intestinal fluid containing bile. All showed bacteriocin activity against Bacillus subtilis. However, only isolates 1C10, 2C10 and 2Y9 had bacteriocin activity against Staphylococcus aureus. Isolate 1Y9 was the most tolerant to artificial gastric juice at pH 2 and 3C10 showed the highest tolerance to simulated intestinal fluid containing bile. Because the three isolates 1Y9,3C10 and 1C10 tolerate pH 3 and bile, and exhibit antimicrobial activities, they may be considered probiotic cultures. Based on the results of probiotic property tests, isolate 3C10 was used to develop probiotic white soft cheese ('kesong puti') and milk confectionery ('pastillas de leche'). Lb. paracasei survived the conditions in the 'kesong puti' and 'pastillas de leche' with mean viable counts after 1 wk storage of 3.0 x 109 CFU g -1 and 4.9 x 106 CFU g-1, respectively. The response surface plot showed that viable counts of 'kesong puti' increased with an increase in culture level up to 1 wk refrigerated storage, after which, viable counts decreased. Increasing the level of Lb. paracasei caused a highly significant increase in yield, protein, fat and ash content of the 'kesong puti'. Response surface plot of viable count vs. Lb. paracasei cell concentration in the 'pastillas de leche' and storage period showed that 10 8 CFU g-1 and 1 wk storage at room temperature will guarantee the minimum therapeutic daily dose of 108-109 viable cells. No differences in acceptability scores between treatments were observed. Increasing the cell concentration of Lb. paracasei caused a highly significant increase in the yield, protein content and ash content of 'pastillas de leche.
Keywords: Dairy products; Probiotics